2014
DOI: 10.1007/s00348-014-1685-9
|View full text |Cite
|
Sign up to set email alerts
|

Scalar dissipation rate measurements in a starting jet

Abstract: Measurements of the scalar dissipation rate are performed in an impulsively started gas jet, using planar laser induced fluorescence. The measurements are well resolved spatially. The deteriorating effect of experimental noise on this experiment is treated with a Wiener filter, which is shown to be applicable to this large-scale inhomogeneous flow. The accuracy of the scalar dissipation rate is within 20%, as determined from an explicit calculation of the filtering errors. The residual fields that remain after… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The jet penetration was found to scale linearly with time until the jet tip reaches a certain distance from the nozzle exit; afterwards, the jet penetration scales with the square root of time [33] . Soulopoulos et al [34] performed scalar dissipation rate measurements in a starting jet and found that high values of scalar dissipation rate were concentrated at the jet boundary as well as at random regions in the jet body.…”
Section: Introductionmentioning
confidence: 98%
“…The jet penetration was found to scale linearly with time until the jet tip reaches a certain distance from the nozzle exit; afterwards, the jet penetration scales with the square root of time [33] . Soulopoulos et al [34] performed scalar dissipation rate measurements in a starting jet and found that high values of scalar dissipation rate were concentrated at the jet boundary as well as at random regions in the jet body.…”
Section: Introductionmentioning
confidence: 98%
“…More details on the experimental setup, the data processing and the error assessment are provided in Ref. 36.…”
Section: Flow Arrangement and Measurement Methodsmentioning
confidence: 99%
“…In the current work, the PSF is represented by a Gaussian profile, which is expected for most of the optical systems without the presence of an image intensifier that alters the PSF with a longer tail. In the context of fluid mechanics, where the Wiener Filter is applied to the two-dimensional velocity vector field, the estimation of spectral density of noise and un-blurred noise-free 'image' is achieved via kinetic energy power spectrum following the approach of Soulopoulos et al (2014). The kinetic energy power spectrum of the turbulent flow condition, detailed in Table 1, is shown in Fig.…”
Section: The Wiener Filter and The Median Filtermentioning
confidence: 99%
“…5. According to the procedure described by Soulopoulos et al (2014), power spectral density estimation is shown in Fig. 5.…”
Section: The Wiener Filter and The Median Filtermentioning
confidence: 99%
See 1 more Smart Citation